Salmonella Paratyphi A infection of a Thyroid Cyst - Qamar, Salima; Irfan, Seema (Infectious Diseases Journal of Pakistan, 2022)
We report a case of infected thyroid cyst with Salmonella Paratyphi A in 64 years old patient who presented with short history of fever and neck pain. Ultrasound neck showed thyroid cyst for which fine needle aspiration was done. Culture of aspirated fluid grew Salmonella Paratyphi A. Patient was treated successfully with Ceftriaxone. Blood or other site cultures were not sent so source of origin could not be determined. Suppurative infections of thyroid gland are uncommon1 due to high levels of iodine within the gland however, in rare cases thyroid gland may get infected in case of underlying thyroid disorders like neoplastic or autoimmune diseases. In current case, no underlying thyroid related abnormality was found. Based on short duration of illness found in case history, this case appears as an example of acute thyroiditis caused by Salmonella Paratyphi A. In conclusion, infectious thyroiditis caused by Salmonella Paratyphi A is rare and may be encountered in patients with or without prior comorbid or immunosuppression.